Digital marketing strategies in the company CORPIEL S.A.C – Lima, 2022 - Seminario Unzueta, Randall Jesús (2022)
Objective: determine the digital marketing strategies in the commercial area of the company Corpiel S.A.C – Lima, 2022. Material and method: The study has a qualitative approach, applied type, its design is non-experimental, correlational and cross-sectional, with a population of 300 clients over 18 years of age of both sexes who will visit the Corpiel S.A.C store, the data collection technique was the survey and the data collection instrument was the questionnaire, comprised of 24 items for the digital marketing variable grouped into 4 dimensions. Results: the digital marketing strategy related to content is at a very high level with 65%, according to consumers it is at a very high level with 68%, according to the connection 67% with a very high level and in function to the community is at a very high level with 70%. Conclusions: Regarding the digital marketing strategy related to content, we have to work so that customers find clear and precise information about the products and the service that we provide in person and online.